LARVICIDAL EFFECT OF Cuminum cyminum L. CRUDE EXTRACT ON THE LARVAE OF THE IXODID TICK Hyalomma anatolicum - Mohammed Hassan Banaga, Omima; Siddig Mohammed, Ali; Subki Khalid, Hassan (Journal of Veterinary Medicine and Animal Production, 2022)
Cuminum cyminum crude water extract was assessed against ten days old larvae of Hyalomma anatolicum. Serial two fold dilutions starting from 50% and downwards to 0.78% were assessed using a locally made device to enable exposure of larvae to the effect of the volatile extract, while the control group was exposed to water vapour only. To determine the lower lethal concentration, larvae were exposed to serial dilutions down to 0.00009%. The results showed 100% mortality at 0.0121% dilution and above. The effective exposure time was tested using 0.78% concentration, where it was found to increase from 32.61% in the first hour to 100% in the fourth hour. The time to kill 50 % T50 was 1.24 hour, while T100 was 3.51 hours. In regards to the residual effect, larval mortality after overnight exposure was 34%, 19.7%, 13.1%, 6.7%, 2.3% and 1.3% in the first to the sixth hour, respectively.